GE_GERICHTE C/16132/2017 vom 22. Juni 2018 - GE Cour de justice (2018)
MESURE PROVISIONNELLE ; REGISTRE DU COMMERCE ; SOCIÉTÉ ANONYME ; CONSEIL D'ADMINISTRATION ; MEMBRE | CPC.261.al1; CO.706.al1; CO.706b.al1; CO.699; CO.700.al3; CO.933